Single dose artemisinin-mefloquine treatment for acute uncomplicated falciparum malaria. - Tran, T; Arnold, K; Nguyen, T; Pham, P; Nguyen, T; Bui, M; Le, M; Mach, Q; Le, H; Pham, P (1994)
For the treatment of patients with acute falciparum malaria, the combination of artemisinin as a single dose with a single dose of mefloquine was studied in 4 separate prospective trials, comprising 405 adults and 139 children with uncomplicated falciparum malaria in 2 in-patient and 2 rural out-patient studies in Viet Nam. Adults received oral artemisinin and children artemisinin suppositories. Randomized comparative treatment schedules were: artemisinin alone for 5 d, mefloquine-sulfadoxine-pyrimethamine (MSP), or quinine plus sulfadoxine-pyrimethamine (SP). Parasite clearance times (PCT) were rapid for artemisinin treated inpatients (90%: 14.8-20.4 h) but also for patients receiving MSP (PCT 90%: 18.0 h) and quinine (PCT 90%: 22.5 h). The recrudescence rate (RI) during a 28 d follow-up period among the patients given artemisinin plus mefloquine was 15% in the adult in-patients and zero in the adult and children out-patients. RI in the artemisinin 5 d treatment group was 33.3%; among those given artemisinin plus SP it was 47.3% in in-patients and in out-patients 46.1%. In the MSP treated out-patients RI was 1.5% in adults and zero in children. Artemisinin as a single dose (oral in adults and as a suppository in children) in combination with mefloquine was effective in rapidly lowering parasitaemia and in preventing recrudescence in hospital in-patients and in out-patients attending a rural health clinic. MSP alone as a single dose also rapidly reduced parasitaemia (but not as quickly as the artemisinin-mefloquine combination in out-patient children) and prevented recrudescence.